Upaya Pemimpin Pesantren Dalam Penguatan Nilai-Nilai Karakter Guru Di Pondok Modern Tazakka Bandar Kabupaten Batang Tahun 2014-2016 - Ziaur Rahman Abdullah, Rifki, Dr. Syamsul Hidayat, M.Ag (2016)
Character education is the most important provision for the younger generation who will lead Indonesia today. The condition of Indonesia is categorized under crisis conditions, even not just one crisis but a multidimensional crisis. this can be seen from deviant behavior committed by students such, promiscuity, drug use, fighting between the school to homicides to terminate their future. From the above phenomena of character education to be one of the main solutions in solving the problem. To obtain maximum results, which makes the students have a strong character, it is necessary also a teacher of character. This in research, issues that became the focal point of research is Any character values boosted by pesantren leaders to teachers and how efforts pesantren leaders in strengthening character values teachers. While the benefits are expected to add insight and scientific treasures, especially in strengthening the character of the teacher, and can be used as a reference for future research and can provide input and contribute ideas to improve the quality of education in the formation of character. This study is a qualitative research background is penelitaian pesantren leaders Pondok Modern Tazakka Bandar Batang District. Field methods of data collection used by documentation, observation and interviews. While the data analysis methods used are interactive cycle analysis that takes data from the field, then summarize and correlating information from the data obtained and then a conclusion. according to the leader of Pondok Modern Tazakka character values that must be owned by duru namely, trust, sincerity, authoritative, attractive appearance, simplicity, enforcement of discipline and have extensive knowledge. In instilling the values of these characters, the leader of the three schools apply leadership models that are run by leaders of pesantren. Three models of leadership that these applied that is, religio-paternalistic leadership, paternalistic-authoritarian leadership, legal-formal leadership, and use some other strategy.